Interactive Multimedia in Differentiated Learning to Improve identifying of Simple Past Tense sentences in Vocational High School Students - Rahmawati Upa; Hafirah Patang; Paldy Paldy; Inrawati Inrawati (Jurnal Studi Guru dan Pembelajaran, 2024)
This study aims to improve students' ability to identify simple past tense sentences through the use of interactive multimedia and differentiated instruction in the classroom. The context of English language learning, many students struggle to understand grammar material, particularly in recognizing the correct tense structure in sentences. Therefore, this study focuses on implementing methods that can help students better understand the use of the simple past tense effectively. The study uses a classroom action research method carried out in two cycles. The first cycle began with the use of an interactive video, followed by group discussions and individual assessments. The results showed that despite the implementation of content and process differentiation, most students did not meet the desired target. The second cycle, improvements were made through homogeneous grouping, more frequent pauses in the video, and increased support for students with lower competencies. The results of the second cycle showed a clear improvement in students' abilities, with 53% of students achieving the "Excellent" category and 42% in the "Good" category. These findings indicate that the application of appropriate differentiation strategies, structured multimedia use, and additional support for students with lower competencies can enhance students' learning outcomes in identifying simple past tense sentences. This study also emphasizes the importance of continuous reflection in teaching to improve English learning outcomes.